1982
DOI: 10.1073/pnas.79.4.1269
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the genetically determined acetylator phenotype and DNA damage induced by hydralazine and 2-aminofluorene in cultured rabbit hepatocytes.

Abstract: The relationship between acetylation rates of rabbit hepatocytes and their susceptibility to genotoxicity by DNAdamaging chemicals that undergo N-acetylation was studied in primary cultures of hepatocytes from New Zealand White rabbits that have a genetically determined difference in acetylation rates. Hepatocytes from rapid and slow acetylator rabbits maintained in culture the difference in acetylation rates that existed in viva DNA repair, an index of DNA damage, was produced by hydralazine in hepatocytes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Hydralazine induced DNA repair in rat and rabbit hepatocytes McQueen et al, 1982), but no DNA repair was observed in hepatocytes from C57B1/6 mice. Additionally, genetically determined differences in the biotransformation of hydralazine resulted in a difference in the susceptibility of the cells from the same species to the genotoxic effect of the chemical.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydralazine induced DNA repair in rat and rabbit hepatocytes McQueen et al, 1982), but no DNA repair was observed in hepatocytes from C57B1/6 mice. Additionally, genetically determined differences in the biotransformation of hydralazine resulted in a difference in the susceptibility of the cells from the same species to the genotoxic effect of the chemical.…”
Section: Resultsmentioning
confidence: 99%
“…The method for isolating rat hepatocytes (Williams, 1976;Williams et al, 1982) has been modified for use with mouse, hamster, rabbit and guinea pig (McQueen et al, , 1982(McQueen et al, , 1983aMaslansky and Williams, 1985a). Cells are isolated from young adult animals by a two-step in situ perfusion of the liver.…”
Section: Isolation Of Hepatocytes and Initiation Of Monolayermentioning
confidence: 99%
See 1 more Smart Citation
“…Various enzyme systems, such as cytochrome P-450-dependent N-hydroxylase (Miller and Miller, 1969;Felton et al, 1976), sulfotransferase (De Braun et al, 1970;Meerman et al, 1981), Nacetyltransferase (Brouns et al, 1981, McQueen et al, 1982, N-O-acetyltransferase (Weeks et al, 1978, King andGlowinski, 1983), deacetylase (Schut et al, 1978), UDP-glucuronyl-transferase (Irving, 1971), prostaglandin endoperoxide synthetase (Boyd et al, 1983) and peroxidase (Walker and Floyd, 1979) have all been proposed to be important in the conversion of AAF and AF to their ultimate carcinogenic forms. Many of the apparent discrepancies regarding the relative importance of these enzymes in the activation of AAF and AF which have been reported may possibly be due to the different endpoints used in the various studies.…”
mentioning
confidence: 99%
“…Firstly, it may have direct application in diseases such as ulcerative colitis and rheumatoid arthiris where steroids and sulphasalazine are frequently coprescribed. Secondly, it may influence the genotoxicity of several arylamines which are metabolically activated by NAT (Glowinski et al, 1978;McQueen et al, 1982McQueen et al, , 1983. In the present communication, we have investigated the effect of intra-articular corticosteroids on the disposition of sulphadimidine in patients with osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%